2012
DOI: 10.3109/00016489.2012.699195
|View full text |Cite
|
Sign up to set email alerts
|

Using intravital microscopy to observe bevacizumab-mediated anti-angiogenesis in human head and neck squamous cell carcinoma xenografts

Abstract: We found significant effects of bevacizumab on angiogenesis and cancer cell survival in HNSCC. Repeated injections of bevacizumab were found to provide the greatest effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 17 publications
1
2
0
Order By: Relevance
“…A previous study from our laboratory showed that high VEGF expression was significantly related to a decrease in survival, whereas loss of VEGF results in a significantly improved prognosis . Furthermore, Yamatodani et al reported significant inhibitions of bevacizumab on angiogenesis and cancer cell survival in HNSCC . Our results indicate that hypermethylation of GALR2 with a high expression of VEGF is associated with a DFS rate of 10.5%, compared with 52.2% for other conditions (log‐rank test, P = .0096) (Fig.…”
Section: Discussionsupporting
confidence: 54%
“…A previous study from our laboratory showed that high VEGF expression was significantly related to a decrease in survival, whereas loss of VEGF results in a significantly improved prognosis . Furthermore, Yamatodani et al reported significant inhibitions of bevacizumab on angiogenesis and cancer cell survival in HNSCC . Our results indicate that hypermethylation of GALR2 with a high expression of VEGF is associated with a DFS rate of 10.5%, compared with 52.2% for other conditions (log‐rank test, P = .0096) (Fig.…”
Section: Discussionsupporting
confidence: 54%
“…Innovative drug delivery systems visualized by IVM utilizing nanoparticles to enhance tumor responses offer unique approaches to augment the efficacy of chemotherapeutic agents [ 16 , 64 , 65 ]. Tumor vessel responses to anti-angiogenic drugs such as bevacizumab can also be directly observed over time with IVM [ 55 , 66 ], which have shown partial restoration of normal vessel permeability and interstitial fluid pressures that equate to enhanced anti-tumor responses. In summary, IVM has and continues to provide novel information regarding tumor vasculature, blood flow, and drug delivery in preclinical cancer models.…”
Section: Ivm In the Study Of Tumor Vasculaturementioning
confidence: 99%
“…Bevacizumab, an anti-vascular endothelial growth factor monoclonal antibody, was the first anti-angiogenesis agent to receive US Food and Drug Administration approval in oncology [ 16 ]. Numerous studies of the bevacizumab showed promise in patients with squamous cell carcinoma of the head and neck (SCCHN) [ 17 , 18 ]. Nylfot, MJ et al reported that bevacizumab could reduce tumor proliferative capacity of SCCHN, and combined bevacizumab with cisplatin-based chemo-radiation therapy for SCCHN revealed safe and significant responses [ 19 ].…”
Section: Discussionmentioning
confidence: 99%